(untitled) (Information systems and technologies security, 2020)
Open and free cyberspace increases the freedom of people and social communications, in such conditions it becomes especially important to search for new possibilities of ensuring the state security in view of the formation of a new confrontation field - cyberspace. It is important to analyze the actual problems of information security, actions of the world governments and world organizations for identifying the current state of modern trends in the cybersecurity field. Cybersecurity incidents affect the lives of consumers of informational and many other services, and cyberattacks targeting various objects of electronic communications infrastructure or process management. This article covers in detail the factors that influence the state of cybersecurity in the country, its cyberspace and the protection of information objects. The rapid development of malicious software in the world and the lines of action by famous hacker groups are analyzed. The tendencies of active legislative updates in the cybersecurity field of the world’s leading countries, such as creating new structural groups, increasing the number of existing ones and increasing their funding, are identified. The reasons for attackers concentrating their efforts on the search for assets vulnerabilities and the development of a unique multifunctional malware and technologies for unauthorized assets are considered. Structured information about the status of modern trends in the field of cybersecurity and information protection is presented in this article. The situation that has evolved to date with cybercrime requires continuous improvement of cybercrime fighting methods, development of information systems and methods aimed at ensuring the country’s cybersecurity. Therefore, the issue of cyberspace security, cybercrime fighting is relevant internationally as well as at the national level and therefore needs further consideration.